The Moroccan Model of Public Governance: Current Situation in Morocco - NAFZAOUI, Mohammed Achraf; FERDOUSSI, Soukayna (Revue Internationale du Chercheur, 2024)
In recent years, Morocco has embarked on a journey towards a new model of public governance aimed at enhancing transparency, efficiency, and accountability in the management of public finances. This transformation is grounded in a strategic shift towards multi-year budget programming and program-based budgeting, aligning resource allocation with anticipated outcomes. Known as New Public Governance, this approach emphasizes performance-oriented management and rigorous evaluation of public policy effectiveness. NPG also seeks to foster stakeholder engagement, ensuring decisions are legitimate and backed by transparent fiscal practices. Despite substantial progress, challenges persist, including the need to strengthen institutional capacities, improve performance monitoring, and adapt swiftly to economic and social changes. Organizational hurdles, such as inter-ministerial coordination and resource mobilization for ongoing reforms, further complicate implementation. Moreover, resistance to change within administrative structures and the demand for comprehensive staff training remain significant obstacles. This paper underscores Morocco's efforts to modernize its public financial governance, navigating global economic uncertainties while striving to meet international standards and address domestic imperatives.